Trade‐offs between constitutive and induced defences drive geographical and climatic clines in pine chemical defences. (19th February 2014) - Moreira, Xoaquín; Mooney, Kailen A.; Rasmann, Sergio; Petry, William K.; Carrillo‐Gavilán, Amparo; Zas, Rafael; Sampedro, Luis; Novotny, Vojtech
Abstract There is increasing evidence that geographic and climatic clines drive the patterns of plant defence allocation and defensive strategies. We quantified early growth rate and both constitutive and inducible chemical defences of 18 Pinaceae species in a common greenhouse environment and assessed their defensive allocation with respect to each species' range across climatic gradients spanning 31o latitude and 2300 m elevation. Constitutive defences traded‐off with induced defences, and these defensive strategies were associated with growth rate such that slow‐growing species invested more in constitutive defence, whereas fast‐growing species invested more in inducible defence. The position of each pine species along this trade‐off axis was in turn associated with geography; moving poleward and to higher elevations, growth rate and inducible defences decreased, while constitutive defence increased. These geographic patterns in plant defence were most strongly associated with variation in temperature. Climatic and geographical clines thus act as drivers of defence profiles by mediating the constraints imposed by trade‐offs, and this dynamic underlays global patterns of defence allocation.